Cy Twombly : fotografisch werk 1951-2010 = oeuvre photographique 1951-2010 - Twombly, Cy. (Antwerpen : Bozar Books ; Ludion, 2012)
Twombly's photographic oeuvre, which did not achieve recognition until late, spans more than sixty years of his career. In this catalogue around a hundred unpublished photographs selected,(just before his death), by the artist himself, he also did the book design. The photographs are accompanied by an essay written by Hubertus V. Amelunxen.00Exhibition: Paleis voor Schone Kunsten, Brussels. February/April 2012.
boek
Keywords: Twombly, Cy